Characterization of Ornamental Rock Residue and Potassium Liberation Via Organic Acid Application - Machado,Ramires Ventura (2016)
ABSTRACT Organic acids present in organic matter and, or, exudates by microorganisms and plants can increase the liberation of potassium present in minerals. The objective of this study was to characterize the residue from ornamental rocks and evaluate the release of K from these residues after the application of organic acids. The experiment was conducted under laboratory conditions and followed a 2 × 3 × 5 factorial design with three replicates. The studied factors were: two organic acids (citric acid and malic acid), three ornamental rock residues (R1, R2 and R3) and five organic acid rates (0, 5, 10, 20 and 40 mmol L-1). After agitation, K concentrations were determined in the equilibrium solution. Successive extractions were performed (1, 5, 10, 15, 30 and 60 days after the start of the experiment). The organic acids used (citric and malic) promoted the release of up to 4.86 and 4.34 % of the total K contained in the residue, respectively, reinforcing the role of organic acids in the weathering of minerals and in providing K to the soil. The K quantities were, on average, 6.1 % higher when extracted with citric acid compared to malic acid.